Giant coronary aneurysm presenting as a cardiac mass on transthoracic echocardiogram. (20th March 2014) - Mutha, Vivek; Asrar ul Haq, Muhammad; Anavekar, Nagesh S; Barlis, Peter
Abstract : A 69-year-old man with a history of ischaemic heart disease and previous stent implantation in the right coronary artery (RCA) was found to have a large well-encapsulated mass attached to the right atrium on a routine transthoracic echocardiogram. Subsequent investigations including transoesophageal echocardiography and CT coronary angiogram suggested an RCA aneurysm formation in relation to the prior stented segment, further confirming on coronary angiogram a large ectatic vessel with a giant aneurysm measuring 2.4×2.7 cm. Giant coronary artery aneurysms are rare and here we present interesting images of a case initially picked up on transthoracic echocardiography.